ANALISIS VALUASI SAHAM BUMN MENGGUNAKAN METODE DIVIDEND DISCOUNTED MODEL DAN ECONOMIC VALUE ADDED - Irvan Liunardi Senjaya (Jurnal Administrasi Bisnis, 2021)
This research is aimed at analyzing the valuation of BUMN shares with the dividend discounted model and economic value added model. This study is also aimed to teach early or novice investors about financial statement analysis, which contains information about companies' finances and companies' actions in the following years. Financial statement analysis is not limited to the Price-to-Earnings Ratio (P/E Ratio) and Price-to-Book Value (PBV). There are various analyses that can be used, such as the dividend discounted model aiming to find the company's intrinsic value and economic value added aiming to find economic value that will benefit investors. For this research, the researchers need 12 state-owned-enterprises (SOEs) to be used as samples and secondary data. The data used for this research are financial statements (2015-2019 period) and dividends per share (2015-2019 period). The data used were obtained before the event of CoVID-19. The results show that from the dividend discounted model and economic value added, 7 out of 12 SOEs are undervalued and have economic value for investors.